2021
DOI: 10.1111/dom.14364
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic inertia in the management of dyslipidaemia and hypertension in incident type 2 diabetes and the resulting risk factor burden: Real‐world evidence from primary care

Abstract: Objective: To investigate trends in the prevalence of hypertension and dyslipidaemia in incident type 2 diabetes (T2DM), time to antihypertensive (AHT) and lipid-lowering therapy (LLT), and the association with systolic blood pressure (SBP) and lipid control.Research Design and Methods: Using The Health Improvement Network UK primary care database, 254 925 people with incident T2DM and existing dyslipidaemia or hypertension were identified. Among those without atherosclerotic cardiovascular disease (ASCVD) his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…In 2021, a study was conducted on therapeutic inertia in dyslipidemia and hypertension in patients with type 2 diabetes mellitus [ 42 ]. The authors observed a significant delay in initiating treatment for primary prevention in both cases, regardless of cardiovascular risk, and in all age groups.…”
Section: Discussionmentioning
confidence: 99%
“…In 2021, a study was conducted on therapeutic inertia in dyslipidemia and hypertension in patients with type 2 diabetes mellitus [ 42 ]. The authors observed a significant delay in initiating treatment for primary prevention in both cases, regardless of cardiovascular risk, and in all age groups.…”
Section: Discussionmentioning
confidence: 99%
“…In the IMPROVE-IT study, in the subgroup of patients with diabetes, ezetimibe in addition to simvastatin was particularly effective, reducing the relative risk by 15% (95% CI: 6-22%), and the absolute risk by 5.5% [297]. The FOURIER study demonstrated that therapy with a PCSK9 inhibitor provides similar benefits in pa- Very high Type 2 diabetes with organ damage 1 or other major risk factors 2,3 , type 1 diabetes with early onset and duration > 20 years…”
Section: Pharmacotherapy Of Lipid Disorders In Patients With Diabetesmentioning
confidence: 99%
“…The significance of therapeutic inertia, either in the form of inadequate therapy (usually the lack of intensive statin treatment or, even less likely, combination therapy) or evident errors such as dose reduction or cessation of treatment following achievement of the therapeutic target, also cannot be diminished. That is why in Poland there are still nearly 20 million individuals with hypercholesterolaemia, most of them unaware of their condition [ 3 ]; that is why only ca. 5% of patients with familial hypercholesterolaemia out of predicted as much as 140,000 have been diagnosed; that is why other rare cholesterol metabolism disorders are so rarely diagnosed in Poland [ 4 , 5 ].…”
Section: Preamble Why Do We Need New Guidelines In 2021?mentioning
confidence: 99%
“…Organ damage is defined as the presence of microalbuminuria, retinopathy, neuropathy, and/or left ventricular muscle damage; 2 other means at least 2 or more;3 major risk factors include: age ≥ 65 years, hypertension, dyslipidaemia, tobacco smoking, obesity; 4 not applicable to type 1 diabetes in young adults (< 35 years of age) with duration of diabetes < 10 years.…”
mentioning
confidence: 99%